Efficacy, safety, and controversy of ultrasound-guided radiofrequency ablation in the treatment of T1N0M0 papillary thyroid carcinoma - Yi, Zhang; Siyu, Li; Lijun, Fu; Danhua, Zhang; Jianhua, Li; Xinguang, Qiu (Frontiers in Oncology, 2022)
Objective To evaluate the safety effect, and controversy on the treatment outcomes of radiofrequency ablation (RFA) for T1N0M0 papillary thyroid carcinoma (PTC). Materials and methods This study is assessed the medical records of 142 patients with primary T1N0M0 PTC tumors after RFA between 2014 and 2022. 4 patients underwent delayed surgery (DS) after RFA and 411 T1N0M0 patients underwent DS were recorded. Outcomes were compared between RFA and DS groups after propensity score matching (PSM). Results The maximal diameter (MD) and volume (V) increased in months 1 (P < 0.01) and reduced after the 6-month follow-up (all P < 0.01). The disappearance and disease progression rates were 53.5% and 2.1%, respectively. The complication and disease progression rates had no significant difference between RFA and DS (P>0.05). In some cases, the tumors were not fully inactivated after RFA, and the central compartment lymph node (CCLN) were metastasis. The CCLN metastasis rate was 13.4%. MD, V and clustered calcifications were independent risk factors for CCLN metastasis by univariate analysis. Conclusions RFA is an effective and safe treatment option in selected patients with solitary T1N0M0 PTC. There are the risks of tumor incompletely ablated and CCLN metastasis.